CHARACTER EDUCATION MUHAMMADIYAH PATTERN (Case Study SMA Muhammadiyah 1 and MA Muallimin Yogyakarta) - Kuswono, Kuswono (Universitas Muhammadiyah Metro, 2013)
Abstrak: This research aims to find out the sources of character education at Islamic schools, character- building values application and actualization. This research was conducted in SMA Mubammadiyah I Yogyakarta and MA Muallimin Muhammadiyah Yogyakarta. The result of research showed that teacher's perception on character education relied on Islamic precepts to create akhakul karimah-human beings. The sources of character education included Quran and as=Sunnah/Hadist as well as Ijtihad. The character value implantation was carried out through learning in the classroom, precedents from figures, teachers and peers, well-behaving familiarization in the presence of rule and order, personality report, and extracurricular activities in knowledge, skill, sport, art, and organization fields. The form of character-building values actualization emphasized more on the Islamic activities such as collectively shalat, reading and reciting Quran, social service, participating actively in IPM, hizbul wathan, and tapak suci organizational activities. In addition, there were kader inti/an, mubalig jumat, mubalig hijarah, fasting, Friday sermon, becoming the orator in pengajian, and flag ceremony. Such these activities reflected on religious, cooperative, leadership, loving-to-homeland, social care, environmental care, and creative values.Keywords: Education, Character, Muhammadiyah.